Sound Field Modelling and Noise Reduction for a Forklift Power Compartment Based on Perfectly Matched Layer and Acoustic Packaging Design - ZHANG, Enlai; LIU, Zhiqi; ZHANG, Jingjing; LIN, Jiahe (Archives of Acoustics, 2021)
The core goal of this paper is to put forward a feasible scheme of noise reduction for a target forklift on the basis of solving the problem of vibration and acoustic radiation from complex structures in infinite domain. Based on the previous report and vibration acceleration tests, the acoustic virtual wind tunnel model of forklift power compartment was established using finite element method and boundary element method, in which the perfectly matched layer was first applied to simulate the attenuation propagation of sound waves in air. In addition, according to the distribution characteristics of sound pressure field with different frequencies, the acoustic energy mainly radiated through the bottom and right side, and concentrated in the low frequency. Consequently, the acoustic packaging design for the whole forklift power compartment was presented, and a satisfying noise reduction effect was achieved.